1984
DOI: 10.1021/ma00141a032
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic ring flips in a semicrystalline polymer

Abstract: 27) It is interesting to note that in phase II (a) of PVDF the closest H-F distances are not all to the fluorine atoms on adjacent carbon atoms. The shortest H-F distances of HI, for instance, are to F2 and F3, on adjacent different carbon atoms and to FI' and F2' on carbons three bonds removed from the carbon to which HI is connected (see ref 20).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 11 publications
2
49
0
Order By: Relevance
“…Note that even for C 2 jumps around the C para -C ipso axis, the para deuteron is not being averaged by the motion and should give rise to a static powder pattern. For C-2 H bond in phenyl-rings QCC's of 170-180 kHz (and rj = 0) have been reported by several researchers [11,[36][37][38][39], The 2 H line shapes in solid III are characteristic for phenyl-rings performing C 2 flips around the C para -C ipso axis with a jump angle 20 = 120°. At 290 K the C 2 flips are in the intermediate exchange region, allowing one to obtain a jump correlation time from the line shape.…”
Section: Iv) Reorientational Dynamics Of the -C 6 D 5 Groupmentioning
confidence: 93%
See 1 more Smart Citation
“…Note that even for C 2 jumps around the C para -C ipso axis, the para deuteron is not being averaged by the motion and should give rise to a static powder pattern. For C-2 H bond in phenyl-rings QCC's of 170-180 kHz (and rj = 0) have been reported by several researchers [11,[36][37][38][39], The 2 H line shapes in solid III are characteristic for phenyl-rings performing C 2 flips around the C para -C ipso axis with a jump angle 20 = 120°. At 290 K the C 2 flips are in the intermediate exchange region, allowing one to obtain a jump correlation time from the line shape.…”
Section: Iv) Reorientational Dynamics Of the -C 6 D 5 Groupmentioning
confidence: 93%
“…In solid I, at 372 K, a 2 H nmr line shape typical for rotational diffusion of a phenyl-ring around the C para -C ipso axis [37,38] was observed. However, if only small angle diffusion around the C para -C ipso axis takes place, the 2 H nmr line shape should consist of an axially symmetric powder pattern with a quadrupolar splitting of 1/8 times that of a static spectrum and an integrated, normalized intensity of 4/5.…”
Section: Iv) Reorientational Dynamics Of the -C 6 D 5 Groupmentioning
confidence: 99%
“…The simulated spectra perfectly reproduced the observed spectra. In order to confirm the acceleration of the rate of the phenylene dynamics of 1-d 4 at temperatures above 270 K, the temperature dependence of the spin -lattice relaxation time (T 1 ) was investigated (24). The relaxation time, T 1 , for the molecular gyrotops was measured using the inversion-recovery quadrupole echo pulse sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, such a motion has been proposed for. polymers containing aromatic groups in the main chain such as polycarbonate/0 poly(butylene terephtharate) 11 and poly(arylene ether sulfones) 12 on the basis of solid state 2 H and 13 C NMR studies. It has been found that the phenyl ring flip motions are relatively slow.…”
Section: Phb/pet Copolyestermentioning
confidence: 99%